Kontribusi Sektor Potensial Kabupaten Nganjuk dalam Menyerap Tenaga Kerja Wanita Terhadap Tingkat Kemiskinan - Ani Mega Sari; Hendry Cahyono (Jurnal Ekonomika : INDEPENDEN, 2022)
Nganjuk Regency is still faced with the problem of population poverty, the poverty line always fluctuates so that economic growth becomes one of the benchmarks for improving people's welfare. For this reason, the potential sector owned by Nganjuk Regency needs to be developed in order to encourage economic growth. Therefore, this study aims to determine the potential sector of Nganjuk Regency in absorbing female workers against the poverty level with secondary data during 2016-2020. The results of this study indicate that there are five basic LQ sectors as the rate of economic growth. Then the Shift-Share (SS) analysis shows the performance of each sector in Nganjuk Regency where the agricultural sector has high growth compared to East Java. The manufacturing sector, the health service sector and social activities, the construction sector, the wholesale and retail procurement sector, car and motorcycle repair, and the information and communication sector can progress quickly and have high competitiveness in Nganjuk Regency. Meanwhile, the potential sectors that are able to absorb female workers to the poverty level in Nganjuk Regency are agriculture, manufacturing, and services.